The Effect of Region's Socio-Economic and Demographic Charateristic on Covid-19 Confirmed Cases and Deaths - Abyan Rai (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
Covid-19 pandemic that has hit the world has made almost all countries limit the mobility of their residents to prevent the transmission of the Corona virus. Indonesia has also made similar efforts through Large-Scale Social Restrictions (PSBB). However, these efforts have not been optimal because they are faced with obstacles to the uneven distribution of the population and unfavorable socio-economic conditions. This study aims to analyze the effect of regional socio-economic and demographic characteristics on Covid-19 in terms of the number of confirmed cases and deaths. The analysis was conducted at the provincial level with a total of 34 observations and using multiple linear regression analysis. Socio-economic characteristics are approximated by the share of the province's GRDP, the percentage of the poor, and the Human Development Index (HDI). Demographic characteristics are approximated by population density and population projections. This study found that the high confirmed and death cases of Covid-19 were influenced by poor socio-economic conditions, as well as densely populated demographic conditions and a high population of an area. The results of this study also found a significant effect of the provincial GDRP share and HDI on socio-economic characteristics as well as population projections on demographic characteristics on confirmed and Covid-19 deaths cases in Indonesia.